Music and Ceremony at Notre Dame of Paris 500-1550 - Wright, Craig (Cambridge Cambridge University Press, 1989)
This book is a history of the early musical life of the Parisian cathedral of Notre Dame. All aspects of the musical establishment of Notre Dame are covered, from Merovingian times to the period of the wars of religion in France. Nine discrete essays discuss the history of Parisian chant and liturgy and the pattern and structure of the cathedral services in the late Middle Ages; Notre Dame polyphony and the composers most closely associated with the cathedral, among them Leoninus, Perotinus and Philippe de Vitry; the organ and its repertoire; the choir, the musical education and performing traditions; and the relationship of the cathedral to the court.
Keywords: Notre-Dame de Paris (France); Middle Ages (500-1400); Renaissance (1400-1600); Music history; Church; Catholicism; Paris (France)